Effect of crowding on length of stay for common chief complaints in the emergency department: A STROBE cohort study. Issue 44 (November 2017) - Wickman, Linnéa; Svensson, Per; Djärv, Therese
Abstract : Abstract: Crowding in emergency departments (EDs) is associated with long lengths of stay (LOS); however, it is not known whether the effect is equal across different chief complaints. The aim of the study was to compare the effect of crowding on LOS in the 10 most common medical or surgical chief complaints in the ED. All adult visits to a university hospital ED on weekdays between 8 AM and 9 PM in 2012 (n = 19, 200) were stratified based on chief complaint and triage priority. The ED bed occupancy rate was measured and crowding was defined as an occupancy rate over one. The impact of crowding on LOS was calculated for the different groups. During crowding, LOS was longer among all chief complaints ( P ⩽.01) (except for high-acuity patients with wounds, where the study group was very small). During crowding, LOS increased the most among patients with extremity pain/swelling (145% among high-acuity patients, 125% among low-acuity patients) and flank pain (87% among high-acuity patients, 117% among low-acuity patients) and the least among patients with chest pain (32% among high-acuity patients, 45% among low-acuity patients) or arrhythmia (37% among high-acuity patients, 52% among low-acuity patients). The effect of ED crowding on LOS is unequal across different chief complaints. These findings could be used to improve the processing of specific chief complaints in the ED.